Cell-Autonomous Defects in Thymic Epithelial Cells Disrupt Endothelial-Perivascular Cell Interactions in the Mouse Thymus - Bryson, Jerrod L. (Public Library of Science, 2013)
The thymus is composed of multiple stromal elements comprising specialized stromal microenvironments responsible for the development of self-tolerant and self-restricted T cells. Here, we investigated the ontogeny and maturation of the thymic vasculature. We show that endothelial cells initially enter the thymus at E13.5, with PDGFR-β(+) mesenchymal cells following at E14.5. Using an allelic series of the thymic epithelial cell (TEC) specific transcription factor Foxn1, we showed that these events are delayed by 1–2 days in Foxn1 (Δ/Δ) mice, and this phenotype was exacerbated with reduced Foxn1 dosage. At subsequent stages there were fewer capillaries, leaky blood vessels, disrupted endothelium - perivascular cell interactions, endothelial cell vacuolization, and an overall failure of vascular organization. The expression of both VEGF-A and PDGF-B, which are both primarily expressed in vasculature-associated mesenchyme or endothelium in the thymus, were reduced at E13.5 and E15.5 in Foxn1 (Δ/Δ) mice compared with controls. These data suggest that Foxn1 is required in TECs both to recruit endothelial cells and for endothelial cells to communicate with thymic mesenchyme, and for the differentiation of vascular-associated mesenchymal cells. These data show that Foxn1 function in TECs is required for normal thymus size and to generate the cellular and molecular environment needed for normal thymic vascularization. These data further demonstrate a novel TEC-mesenchyme-endothelial interaction required for proper fetal thymus organogenesis.